Deleterious Effects of Polypropylene Microplastic Ingestion in Nile Tilapia (Oreochromis niloticus) - do Nascimento, Luan Souza; de Oliveira, Susana Luporini [UNESP]; da Costa, Camila Carlino [UNESP]; Aracati, Mayumi Fernanda [UNESP]; Rodrigues, Letícia Franchin [UNESP]; Charlie-Silva, Ives [UNESP]; Conde, Gabriel [UNESP]; Mansano, Cleber Fernando Menegasso; Andreani, Dora Ines Kozusny; de Andrade Belo, Marco Antonio (Springer Nature, 2023)
The effect of daily ingestion of polypropylene microplastic on the health of tilapia, Oreochromis niloticus, was evaluated. 60 fish (± 200 g) were placed in 6 aquariums (n = 10, 100 L each), constituting the following treatments: Control (without the addition of polymer), fed with 100 and 500 µg of polypropylene/kg of body weight (b.w.), respectively. After 30 days of feeding, the animals were submitted to blood collection for hemogram and biochemical study and later euthanized for gut microbiological analysis, somatic index of liver, spleen, heart, kidney, stomach, and intestine. In the serum biochemical study, an increase in cholesterol and serum Aspartate Aminotransferase (AST) activity levels was observed in animals treated with 500 µg of polypropylene. Tilapia-fed polypropylene in the diet showed an increase in thrombocyte and total leukocyte counts, marked by a significant increase in the number of circulating lymphocytes. The results of the somatic study revealed a significant increase in the stomach, liver, and heart of tilapia fed with the polymer. Increase in the number of Gram-negative microorganisms and decrease in mesophilic aerobic microorganisms were observed in the gut of fish exposed to the polymer, including a dose-response effect was observed for these analyses. Therefore, tilapias fed daily with diets containing polypropylene for 30 consecutive days showed deleterious effects, resulting in systemic inflammatory disturbs by altering liver functions, leukocyte profile, and organ morphometry, as well as changes in the intestinal microbiota. Such results demonstrate the impairment of fish health, highlighting the need for further studies that evaluate the impact of microplastics on aquatic organisms.
Keywords: Aquaculture; Aquatic ecosystems; Environmental pollution; Fish; Waste